A scientific approach on developing English writing materials for teaching learning process during early post COVID pandemic - Silitonga, Harpen H. P; Sitorus, Parlindungan; Tarihoran, Saurma K.; Sitinjak, Galina; Sitorus, Nurhayati (Linguistics and Culture Review, 2021)
This research finds from need analysis that covers students background, goal, necessities, lacks, wants and learning needs, a new design of English writing materials is vitally needed. The developed writing materials are validated by two experts; teacher and lecturer. Teacher scored 87.3 and lecturer scored 79.3. This score of validation means the English writing material developed by scientific approach are suitable for learning process for early post covid pandemic.